2011
DOI: 10.1016/j.ejvs.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Severe Proximal Aneurysm Neck Angulation: Early Results Using the Endurant Stentgraft System

Abstract: Treatment with the Endurant stentgraft is technically feasible and safe, with satisfactory results in angulated and non-angulated anatomies alike. No sealing length was lost in extremely angulated cases, confirming the device's high conformability. Mid- and long-term data are awaited to verify durability, but early results are promising and challenge current opinion concerning neck angulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 16 publications
1
65
0
1
Order By: Relevance
“…Numerous studies have shown excellent early outcomes and rates of technical success with the Endurant endograft for AAA repair. [5][6][7][8][9][10][11][12][13] We have already published outcomes at 2 years with this endograft in a part of the present study cohort. 6 However, a particular scepticism about the durability of the device has been expressed, considering the high rates of EVAR-related reinterventions in all randomized controlled trials of EVAR compared with open repair.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Numerous studies have shown excellent early outcomes and rates of technical success with the Endurant endograft for AAA repair. [5][6][7][8][9][10][11][12][13] We have already published outcomes at 2 years with this endograft in a part of the present study cohort. 6 However, a particular scepticism about the durability of the device has been expressed, considering the high rates of EVAR-related reinterventions in all randomized controlled trials of EVAR compared with open repair.…”
Section: Discussionmentioning
confidence: 90%
“…6 The early and midterm evaluation of the device's performance revealed encouraging outcomes not only in friendly but also in challenging anatomic scenarios. [6][7][8][9] A number of series proved also early efficacy even outside of the instructions for use (IFU). 7,10 The literature to date still lacks late results with this endograft to prove its durability and effectiveness.…”
mentioning
confidence: 99%
“…Treatment with the Endurant stent graft is technically feasible and safe, with satisfactory results in angulated and nonangulated anatomies alike. 18 Then, this new-generation device implanted in patients with very short aneurysm necks (<10 mm) showed acceptable midterm results. 19 Globally, patients operated on in off-label conditions with Endurant stent graft have no statistically significant different early and midterm results with respect to those patients who have undergone treatment according to the instructions for use.…”
Section: Discussionmentioning
confidence: 94%
“…A retrospective review of patients undergoing EVAR with unfavorable neck anatomy using the C3 Excluder repostitionable stent-graft demonstrated favorable short-term results and significantly reduced the need for proximal extension cuffs [18]. Bastos et al also reported satisfactory early results using the Endurant stent-graft system in severe proximal neck angulation and no sealing length was lost in extremely angulated cases, confirming the device’s high conformability [19]. In addition, Perdikides et al and Albertini et al reported that endovascular repair using a flexible Aorfix stent-graft was feasible in patients with highly angulated necks and mid-term results were acceptable [12,20].…”
Section: Discussionmentioning
confidence: 99%